(3cJGH aj GdeMGVQGJ hGdeMGhQGJs ((3GHQGgje ZdGe YHO Gddg Hf GdSNGhi GdeGQOjfi s)
(3ChdgG (B:s
(3GdMeO ddg Chdi ef MeOg GdMGeOhf hHYO abO SCdfi HYV GNhGfi Cf CLeY dg aUhdkG JTJed Ydi CdaGX HGQYI ai GdeMGVQI s
(3BNQgG (B:s
(3ef aUd ai GdOYGA dGHi efUhQ GdUYGdHi cJHg Edi GdCejQ bGHhS bhdg (B: (3hdG jYOe GdeYGdi hGdecGQe Wdg Hefg hbOQJg hSYI QMeJg Je GdcJGH s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI YGQa MceJ HGdeOjfI GdefhQI (B((3COH (B154) s
Keywords: (3GdCOHs